Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Long-term soil health and microbiome responses to sustainable management under drought stress in tropical coffee agroecosystems - Marina Scalioni Vilela; Lindsey C. Slaughter; Dalyse Toledo Castanheira; Flávio H. V. Medeiros; Márcio R. Nunes; Fernanda C. L. Medeiros; Bruno Montoani Silva; Alisson A. V. Campos; Mauro M. L. Faria; Leandro C. Paiva; Rayan C. Andrade; Milene A. F. Carvalho; et al. (Plant and Soil, 2026)
Background and aims Implementing sustainable crop management to improve soil health can bolster plant and soil resistance to drought stress. This study evaluated the long-term impact of sustainable soil management on soil health in tropical coffee agroecosystems, focusing on how these practices influenced plant yield and quality, as well as soil microbiome composition and function under drought treatment. Methods Plots were selected from a long-term experiment established in January 2016 in Lavras municipality, Minas Gerais State, Brazil, and treatments had been in place for 7 years by the end of the current study. Soil management treatments included: (i) annual coffee husk residue amendment within rows + permanent signal grass ( Urochloa decumbens ) cover between rows (CHUD), (ii) annual agricultural gypsum amendment within rows + permanent signal grass cover between rows (GUD) , and (iii) a control consisting of coffee monoculture with bare soil. Results Combining coffee husk + signal grass management improved chemical, physical, and biological soil health indicators compared to bare soil management. These practices were also associated with higher coffee yield and superior beverage quality. Soil fungal and bacterial communities responded to both management and water availability, and soil functional indicators assessed by enzyme activity showed greater resistance to the drought treatment under coffee husk + signal grass management . Conclusion Overall, this study indicates that combined residue amendment and soil cover may enhance long-term soil and crop responses in this tropical coffee agroecosystem, with evidence of greater resistance of soil functional indicators to the drought treatment used in the incubation assay.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Copepod egg production estimates are biased by female mortality - Wim J. Kimmerer; Anne M. Slaughter; Toni R. Ignoffo (Limnology and Oceanography, 2024)
Egg production rate (EPR, eggs ♀ −1 d −1 ) is a key measure of the nutritional state of metazoans such as copepods. Chlorophyll concentration is most often used to index responses of copepod vital rates to ambient food, but the fits to EPR are often poor. A known but unexplored bias in EPR estimates is the interaction between lifetime reproductive schedules of adult females and their mortality. We examined this interaction for Pseudodiaptomus forbesi , an abundant sac‐spawning calanoid copepod, in the San Francisco Estuary (SFE), USA. The reproductive schedule of P. forbesi comprises a latent period followed by a generally steady rate of clutch production. We used a Bayesian approach to analyze data from two studies which included 141 individual estimates of proportion ovigerous, eggs per clutch, and mortality from 28 sampling events. Proportion ovigerous contributed 95% of the variation in EPR. Mortality was 0.01–0.73 d −1 by one method and ~ 20% higher by another. When mortality was high, most females were young, few were past the latent stage, and ~ 25% were ovigerous. Proportion ovigerous up to 75% occurred only with mortality > ~0.1 d −1 . Adjusting for mortality increased estimates of proportion ovigerous by 3%–88% (median 36%) and allowed for a relationship with chlorophyll, which could not be fitted to the raw data. However, the adjustments increased uncertainty. Given the large effort required, we recommend that others investigate this phenomenon for other species and environments before this adjustment should be recommended for estimating copepod egg production.

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

Diel Behaviors of Zooplankton Interact with Tidal Patterns to Drive Spatial Subsidies in the Northern San Francisco Estuary - Rowan Yelton; Anne M. Slaughter; Wim J. Kimmerer (Estuaries and Coasts, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

When hazard avoidance is not an option: lessons learned from monitoring the postdisaster Oso landslide, USA - Mark E. Reid; Jonathan W. Godt; Richard G. LaHusen; Stephen L. Slaughter; Thomas C. Badger; Brian D. Collins; William H. Schulz; Rex L. Baum; Jeffrey A. Coe; Edwin L. Harp; Kevin M. Schmidt; Richard M. Iverson; et al. (Landslides, 2021)
On 22 March 2014, a massive, catastrophic landslide occurred near Oso, Washington, USA, sweeping more than 1 km across the adjacent valley flats and killing 43 people. For the following 5 weeks, hundreds of workers engaged in an exhaustive search, rescue, and recovery effort directly in the landslide runout path. These workers could not avoid the risks posed by additional large-scale slope collapses. In an effort to ensure worker safety, multiple agencies cooperated to swiftly deploy a monitoring and alerting system consisting of sensors, automated data processing and web-based display, along with defined communication protocols and clear calls to action for emergency management and search personnel. Guided by the principle that an accelerating landslide poses a greater threat than a steadily moving or stationary mass, the system was designed to detect ground motion and vibration using complementary monitoring techniques. Near real-time information was provided by continuous GPS, seismometers/geophones, and extensometers. This information was augmented by repeat-assessment techniques such as terrestrial and aerial laser scanning and time-lapse photography. Fortunately, no major additional landsliding occurred. However, we did detect small headscarp failures as well as slow movement of the remaining landslide mass with the monitoring system. This was an exceptional response situation and the lessons learned are applicable to other landslide disaster crises. They underscore the need for cogent landslide expertise and ready-to-deploy monitoring equipment, the value of using redundant monitoring techniques with distinct goals, the benefit of clearly defined communication protocols, and the importance of continued research into forecasting landslide behavior to allow timely warning.

Growth and reproductive rates of the dominant copepod Pseudodiaptomus forbesi in response to environmental factors and habitat type in the northern San Francisco Estuary - Austin J. Gearty; Toni R. Ignoffo; Anne M. Slaughter; Wim J. Kimmerer (Aquatic Ecology, 2021)

Kinematic and Somatosensory Gains in Infants with Cerebral Palsy After a Multi-Component Upper-Extremity Intervention: A Randomized Controlled Trial - Nathalie L. Maitre; Arnaud Jeanvoine; Paul J. Yoder; Alexandra P. Key; James C. Slaughter; Helen Carey; Amy Needham; Micah M. Murray; Jill Heathcock; Stephanie Burkhardt; Lelia Emery; Kaleigh Hague; et al. (Brain Topography, 2020)

Landslides across the USA: occurrence, susceptibility, and data limitations - Benjamin B. Mirus; Eric S. Jones; Rex L. Baum; Jonathan W. Godt; Stephen Slaughter; Matthew M. Crawford; Jeremy Lancaster; Thomas Stanley; Dalia B. Kirschbaum; William J. Burns; Robert G. Schmitt; Kassandra O. Lindsey; et al. (Landslides, 2020)
Detailed information about landslide occurrence is the foundation for advancing process understanding, susceptibility mapping, and risk reduction. Despite the recent revolution in digital elevation data and remote sensing technologies, landslide mapping remains resource intensive. Consequently, a modern, comprehensive map of landslide occurrence across the United States (USA) has not been compiled. As a first step toward this goal, we present a national-scale compilation of existing, publicly available landslide inventories. This geodatabase can be downloaded in its entirety or viewed through an online, searchable map, with parsimonious attributes and direct links to the contributing sources with additional details. The mapped spatial pattern and concentration of landslides are consistent with prior characterization of susceptibility within the conterminous USA, with some notable exceptions on the West Coast. Although the database is evolving and known to be incomplete in many regions, it confirms that landslides do occur across the country, thus highlighting the importance of our national-scale assessment. The map illustrates regions where high-quality mapping has occurred and, in contrast, where additional resources could improve confidence in landslide characterization. For example, borders between states and other jurisdictions are quite apparent, indicating the variation in approaches to data collection by different agencies and disparity between the resources dedicated to landslide characterization. Further investigations are needed to better assess susceptibility and to determine whether regions with high relief and steep topography, but without mapped landslides, require further landslide inventory mapping. Overall, this map provides a new resource for accessing information about known landslides across the USA.

Neonatal Multisensory Processing in Preterm and Term Infants Predicts Sensory Reactivity and Internalizing Tendencies in Early Childhood - Nathalie L. Maitre; Alexandra P. Key; James C. Slaughter; Paul J. Yoder; Mary Lauren Neel; Céline Richard; Mark T. Wallace; Micah M. Murray (Brain Topography, 2020)
Multisensory processes include the capacity to combine information from the different senses, often improving stimulus representations and behavior. The extent to which multisensory processes are an innate capacity or instead require experience with environmental stimuli remains debated. We addressed this knowledge gap by studying multisensory processes in prematurely born and full-term infants. We recorded 128-channel event-related potentials (ERPs) from a cohort of 55 full-term and 61 preterm neonates (at an equivalent gestational age) in response to auditory, somatosensory, and combined auditory-somatosensory multisensory stimuli. Data were analyzed within an electrical neuroimaging framework, involving unsupervised topographic clustering of the ERP data. Multisensory processing in full-term infants was characterized by a simple linear summation of responses to auditory and somatosensory stimuli alone, which furthermore shared common ERP topographic features. We refer to the ERP topography observed in full-term infants as “typical infantile processing” (TIP). In stark contrast, preterm infants exhibited non-linear responses and topographies less-often characterized by TIP; there were distinct patterns of ERP topographies to multisensory and summed unisensory conditions. We further observed that the better TIP characterized an infant’s ERPs, independently of prematurity, the more typical was the score on the Infant/Toddler Sensory Profile (ITSP) at 12 months of age and the less likely was the child to the show internalizing tendencies at 24 months of age. Collectively, these results highlight striking differences in the brain’s responses to multisensory stimuli in children born prematurely; differences that relate to later sensory and internalizing functions.

Rice Intake and Emerging Concerns on Arsenic in Rice: a Review of the Human Evidence and Methodologic Challenges - Margaret R. Karagas; Tracy Punshon; Matt Davis; Catherine M. Bulka; Francis Slaughter; Despina Karalis; Maria Argos; Habibul Ahsan (Current Environmental Health Reports, 2019)

Spatial Subsidies and Mortality of an Estuarine Copepod Revealed Using a Box Model - Wim J. Kimmerer; Edward S. Gross; Anne M. Slaughter; John R. Durand (Estuaries and Coasts, 2019)

Effects of freshwater flow and phytoplankton biomass on growth, reproduction, and spatial subsidies of the estuarine copepod Pseudodiaptomus forbesi - Wim J. Kimmerer; Toni R. Ignoffo; Karen R. Kayfetz; Anne M. Slaughter (Hydrobiologia, 2018)

Erratum to: Mechanistic insight of platelet apoptosis leading to non-surgical bleeding among heart failure patients supported by continuous-flow left ventricular assist devices - Nandan K. Mondal; Tieluo Li; Zengsheng Chen; Hegang H. Chen; Erik N. Sorensen; Si M. Pham; Michael A. Sobieski; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Molecular and Cellular Biochemistry, 2017)

Mechanistic insight of platelet apoptosis leading to non-surgical bleeding among heart failure patients supported by continuous-flow left ventricular assist devices - Nandan K. Mondal; Tieluo Li; Zengsheng Chen; Hegang H. Chen; Erik N. Sorensen; Si M. Pham; Michael A. Sobieski; Steven C. Koenig; Mark S. Slaughter; Bartley P. Griffith; Zhongjun J. Wu (Molecular and Cellular Biochemistry, 2017)

Comparison of Blood Viscoelasticity in Pediatric and Adult Cardiac Patients - M. Keith Sharp; Mary Gregg; Guy Brock; Neema Nair; Sarina Sahetya; Erle H. Austin; Christopher Mascio; Mark D. Slaughter; George M. Pantalos (Cardiovascular Engineering and Technology, 2017)

Mentoring Strategies and Outcomes of Two Federally Funded Cancer Research Training Programs for Underrepresented Students in the Biomedical Sciences - Marvella E. Ford; Latecia M. Abraham; Anita L. Harrison; Melanie S. Jefferson; Tonya R. Hazelton; Heidi Varner; Kimberly Cannady; Carla S. Frichtel; Omar Bagasra; Leroy Davis; David E. Rivers; Sabra C. Slaughter; et al. (Journal of Cancer Education, 2016)

Trophic Links in the Plankton in the Low Salinity Zone of a Large Temperate Estuary: Top-down Effects of Introduced Copepods - Joanna K. York; George B. McManus; Wim J. Kimmerer; Anne M. Slaughter; Toni R. Ignoffo (Estuaries and Coasts, 2014)

Full Recovery from a Potentially Lethal Dose of Mercuric Chloride - D. Michael G. Beasley; Leo J. Schep; Robin J. Slaughter; Wayne A. Temple; Jonathan M. Michel (Journal of Medical Toxicology, 2014)

Two species of Halimeda, a calcifying genus of tropical macroalgae, are robust to epiphytism by cyanobacteria - Nicholai M. Hensley; Omar L. Elmasri; Emily I. Slaughter; Sara Kappus; Peggy Fong (Aquatic Ecology, 2013)

Apical-Ventricular Cannula for Aortic Valve Bypass Therapy - Kevin G. Soucy; Joel D. Graham; Carrie J. Benzinger; M. Keith Sharp; Guruprasad A. Giridharan; Michael A. Sobieski; Mark S. Slaughter; Steven C. Koenig (Cardiovascular Engineering and Technology, 2013)

Feasibility of Subcutaneous ECG Leads for Synchronized Timing of a Counterpulsation Device - S. Warren; G. A. Giridharan; R. D. Dowling; P. A. Spence; L. Tompkins; Eric Gratz; L. C. Sherwood; M. A. Sobieski; C. R. Bartoli; M. S. Slaughter; Robert S. Keynton; S. C. Koenig (Cardiovascular Engineering and Technology, 2012)

Optimization of agrochemical application in olive groves based on positioning sensor - M. Pérez-Ruiz; J. Agüera; J. A. Gil; D. C. Slaughter (Precision Agriculture, 2011)

Ground truth evaluation of computer vision based 3D reconstruction of synthesized and real plant images - M. Nielsen; H. J. Andersen; D. C. Slaughter; E. Granum (Precision Agriculture, 2007)

High concordance of drug-induced human hepatotoxicity with in vitro cytotoxicity measured in a novel cell-based model using high content screening - P. J. O’Brien; W. Irwin; D. Diaz; E. Howard-Cofield; C. M. Krejsa; M. R. Slaughter; B. Gao; N. Kaludercic; A. Angeline; P. Bernardi; P. Brain; C. Hougham (Archives of Toxicology, 2006)

Photochemical and Microbial Degradation of 2,4,6-Trinitrotoluene (TNT) in a Freshwater Environment - Huey-Min Hwang; L. F. Slaughter; S. M. Cook; Hua Cui (Bulletin of Environmental Contamination and Toxicology, 2000)

Photochemical and Microbial Degradation of 2,4,6-Trinitrotoluene (TNT) in a Freshwater Environment - Huey-Min Hwang; L. F. Slaughter; S. M. Cook; Hua Cui (Bulletin of Environmental Contamination and Toxicology, 2000)

A NIR Technique for Rapid Determination of Soil Mineral Nitrogen - M. R. Ehsani; S. K. Upadhyaya; D. Slaughter; S. Shafii; M. Pelletier (Precision Agriculture, 1999)

Phototransformation of 2,4-Dichloroaniline in a Surface Freshwater Environment: Effects on Microbial Assemblages - H.-M. Hwang; D. McCullum; L. Slaughter (Bulletin of Environmental Contamination and Toxicology, 1998)